Skyjack : a Thea Paris novel - Howe, K. J. (Novelist) (A Thea Paris novel, 2018)
International kidnap-and-ransom expert Thea Paris is escorting two former child soldiers from Kanzi, Africa, to London when their plane is hijacked. As the plane heads for somewhere in the remote Libyan desert, Thea has to figure out how to take back control of the plane without endangering their lives. Behind the skyjacking is a former nemesis, a Sicilian mobster, who after tense negotiations finds himself with Thea at his beck and call. Revealing a deadly conspiracy that connects the dark postwar legacy of World War II to the present, this case will bring all parties to an explosive conclusion.